If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = 6(k + 5) Reorder the terms: 1 = 6(5 + k) 1 = (5 * 6 + k * 6) 1 = (30 + 6k) Solving 1 = 30 + 6k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-6k' to each side of the equation. 1 + -6k = 30 + 6k + -6k Combine like terms: 6k + -6k = 0 1 + -6k = 30 + 0 1 + -6k = 30 Add '-1' to each side of the equation. 1 + -1 + -6k = 30 + -1 Combine like terms: 1 + -1 = 0 0 + -6k = 30 + -1 -6k = 30 + -1 Combine like terms: 30 + -1 = 29 -6k = 29 Divide each side by '-6'. k = -4.833333333 Simplifying k = -4.833333333
| 7(x-4)=3(x-8) | | 4x+3=57-2x | | 2x-47=2(53)-47 | | 6r+11=15-r | | x^2+4x-94=0 | | 4-2(x+5)=4 | | 7(b-2)=4 | | 2(10-3d)+80= | | 3x+2-x=12 | | F(x+8)=3(x+8)-9 | | 7=8(r-6) | | 7(v+4)-3v=2(2v+2)-12 | | 0.04x^2-3.5x+100=10 | | 8x+17=5x+23 | | 18x+54=252 | | y=0.7x-3.6 | | 10+11x=-30+x | | -6(i-3)=2 | | 4x+6(x-4)=16 | | 22+4x=9x+2 | | -9(-6)-5(2)=12 | | 154x=462 | | -9(3)-5(-6)=12 | | 5x+5y+6z-2x+z-8y= | | 4=7(r-3) | | -36=3(x-3)-6x | | 4-5y=-20 | | 9=6(q-6) | | 0=-0.09+1.1x | | 7x-2(4x+23)+12= | | 5+7=2x | | -6(-3)-7(2)=4 |